From beginning to mature: investigating the development of teacher community through Lesson Study - Ni Shuilleabhain, Aoibhinn; Owens, Emma; Seery, Aidan; Hyland, Diarmaid (Frontiers in Education, 2024)
This research investigates the potential of Lesson Study to develop teachers' professional community. Situated in two case study schools, Doone and Crannog (both pseudonyms), where mathematics teachers participated in multiple, successive cycles of Lesson Study over the course of one academic year, the research attempts to tracedetails the development of teacher community through teachers' conversations and reflections. The analysis is based on a framework of professional teacher community which describes discrete phases of development from beginning to mature. Findings from the research suggest that, through teachers' participation in Lesson Study, teachers are provided with opportunities to recognize that colleagues can be a resource for learning and to express commitment to colleagues' growth, both key features in the formation of teacher community. Furthermore, evidence supports the assertion that participating in Lesson Study can provide teachers with opportunities to develop shared understanding, while also productively building on differences in ideas. In supporting the development of teacher community through Lesson Study, findingsFindings may also offer guidance to facilitators of Lesson Study on elements of teachers' collaborative work which may benefit from additional focus, such as on navigating differences in ideas and approaches within a group. This research contributes to the literature on Lesson Study in outlining how this model of professional development may provide a powerful structure within which teacher community can be developed or nurtured.